2012
DOI: 10.1186/1477-7525-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Greek version of the oral health impact profile (OHIP-14) for use among adults

Abstract: BackgroundTo test the validity of the short form of the Oral Health Impact Profile (OHIP-14) for use among adults in Greece.MethodsThe original English version of the OHIP-14 was translated using the forward-backward technique, pilot-tested, and then applied to 211 adults aged 35 years and above. The questionnaire was filled out during face-to-face interviews conducted by one dentist, while individuals were asked to undergo a clinical examination. The internal consistency of the questionnaire was evaluated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
36
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 17 publications
13
36
2
9
Order By: Relevance
“…The result above 0.9 obtained in our study for all 14 items of OHIP-14 (excellent internal consistency), is also confirmed by reports from other research centers. Similar results were obtained in Italy (0.90), Greece (0.90) and Sri Lanka (0.93) [16][17][18]. The results of our study were slightly better than those reported by Ostberg et al, whose results showed that internal consistency measured with Cronbach's alpha was 0.86 for 7 subscales and 0.88 for 14 separate items; similar results were published by Slade who reported high reliability (0.88) [19].…”
Section: Discussionsupporting
confidence: 84%
“…The result above 0.9 obtained in our study for all 14 items of OHIP-14 (excellent internal consistency), is also confirmed by reports from other research centers. Similar results were obtained in Italy (0.90), Greece (0.90) and Sri Lanka (0.93) [16][17][18]. The results of our study were slightly better than those reported by Ostberg et al, whose results showed that internal consistency measured with Cronbach's alpha was 0.86 for 7 subscales and 0.88 for 14 separate items; similar results were published by Slade who reported high reliability (0.88) [19].…”
Section: Discussionsupporting
confidence: 84%
“…Através do índice subjetivo OHIP-14 (Oral Health Impact Profile), foi observado que tanto no T1 quanto no T2, os pacientes colaboradores tiveram um impacto fraco em relação à doença periodontal. Levando em consideração este exposto, alguns trabalhos relataram que pacientes insatisfeitos com sua saúde bucal apresentaram maiores pontuações deste índice (PAPAGIANNOPOULOU et al, 2012;PIRES, 2009;OLIVEIRA;NADANOVSKY, 2005;ALLEN, 2002;LOCKER et al, 2001). Em relação aos resultados desta pesquisa, não houve escores de impacto forte, demonstrando uma boa percepção sobre a saúde bucal dos indivíduos.…”
Section: Artigos Originaisunclassified
“…The evaluation of dental status of the patients and its influence on their quality of life were conducted by the standardized questionnaire OHIP-14, which was translated and adapted into Ukrainian in accordance with the currently accepted methodology recommendations [8,9,11,19].…”
Section: Methodsmentioning
confidence: 99%